Role of fixed investments in economic growth of country: Lithuania in European context - Tvaronavičius, Vytautas; Tvaronavičienė, Manuela (Journal of Business Economics and Management, 2008)
The paper aims to detect character of relationship between fixed investments and economic growth in Lithuania and predict plausible tendencies of further change of considered variables. In order to achieve the indicated task, authors concentrate themselves on two major questions. Firstly, quantitative relationships between investments into major areas of economic activities and Lithuanian economic growth are being estimated. Secondly, comparative analysis of Lithuanian pattern of investment and randomly taken developed European country is being performed. Authors seek to trace how the latter invested during its process of development. Concrete period of observation is being chosen taking into account the current level of Lithuanian economic development. Authors seek to trace plausible consistent patterns of development in terms of relationship between fixed investments and economic growth as countries develop. Obtained results might allow identifying the role of fixed investments, and, if to go further, facilitating forecasts of possible trends of fixed investment and corresponding economic growth.First published online: 14 Oct 2010